Little old lady’s hernia: a case of strangulated obturator hernia in a 88-year-old woman - Valente, Tania; Ferreira, Nuno; Ferreira, Gonçalo; Figueiredo, Arnaldo; Bárbara, Patrícia; Marinho, Ricardo; Hilário, Sandra; Santos, Miguel C. (International Surgery Journal, 2022)
Obturator hernia is an extremely rare type of hernia and an uncommon cause of intestinal obstruction. Diagnosing it represents a challenge due to the lack of specific signs and symptoms. The delay in establishing the diagnosis is responsible for its high rate of mortality. The patients are usually older, emaciated, small women. We presented a case of a small, thin, 88-year-old woman that came to our emergency department with a four-day history of lower abdominal pain, more intense in the left iliac fossa associated with anorexia and constipation. The diagnosis of the left obturator hernia was made intra-operatively. The small bowel, inside the obturator foramen, was necrotic so we made an enterotomy with primary repair of the hernia defect. The patient had post-operative ileus and left inguinal seroma. She was discharged on day 15 post-op with a good recovery. This case report is meant to be an alert for the difficulty of the obturated hernia diagnosis.